Advantages of AlGaN-based deep ultraviolet light-emitting diodes with a superlattice electron blocking layer. (September 2015) - Sun, Pai; Bao, Xianglong; Liu, Songqing; Ye, Chunya; Yuan, Zhaorong; Wu, Yukun; Li, Shuping; Kang, Junyong
Highlights: Deep UVLEDs with different Al mole compositions of conventional EBL were simulated. The results show the optimal Al mole composition of conventional EBL is 80%. Deep UVLEDs with conventional and superlattice EBL were simulated respectively. The results show the performance of deep UVLED with superlattice EBL improves a lot. The reason of the improvement of superlattice EBL deep UVLED was studied. Abstract: The properties of 298 nm AlGaN based deep ultraviolet light-emitting diodes (UV LEDs) with different Al mole compositions in the conventional electron blocking layer (EBL) are discussed in this paper, the optimal Al mole composition of the conventional EBL is identified at 0.8. The improved structure with an AlGaN/AlGaN superlattice (SL) electron blocking layer (EBL) was then investigated numerically. The electrical and optical properties, band diagrams, carrier concentrations, radiative recombination rates and internal quantum efficiency (IQE) were investigated by APSYS software, and results show that the deep UV LED with superlattice EBL performed much better than the conventional EBL deep UV LED, attributed to reduced electrons leakage and increased holes injection.